Laktatnivån i blodet : en prognostisk markör för tikar med pyometra? - Bergström Ledin, Hanna (SLU/Dept. of Clinical Sciences (until 231231), 2011)
The purpose of the present study was to explore if blood lactate levels are increased in bitches with pyometra, and if the lactate measurement could be used as a prognostic indicator and to determine outcome. The present study included 16 bitches with pyometra that were admitted to the University Animal Hospital, Swedish University of Agricultural Sciences, Uppsala, Sweden. For comparison, a control group consisting of 14 healthy staffowned bitches was also evaluated. In all bitches, a physical examination was performed and blood samples for analysis of haematological and biochemical parameters were obtained. In all bitches with pyometra, surgical ovariohysterectomy was performed and a uterine sample for bacteriological culture and identification was collected. The diagnosis pyometra was subsequently confirmed by post-surgical pathological examination.